Frictional properties of multielement coatings (TiZrHfYNbTa)N - Novikov, V.Ju.; Stolbovoy, V.A.; Beresnev, V.M.; Sobol’, O.V.; Nyemchenko, U.S. (Вопросы атомной науки и техники, 2015)
The influence of pressure of nitrogen atmosphere on the structural and phase state and properties of vacuum-arc nitride coatings Ti-Zr-Hf-V-Nb-Ta has been studied. The multi-element nitride coatings deposited in nitrogen, are single-phase with a cubic face-centered cubic lattice (structural type NaCl) excluding the dropping component. The maximum hardness (42.2 GPa) is achieved for the nitride coatings deposited by vacuum arc evaporation (Ti, Zr, Hf, V, Nb, Ta) of the alloy at the pressure of nitrogen of 0.3 Pa. The tribotechnical characteristics have been studied during high temperature tests. It was found that wear resistance of the coatings is higher at T = 500 °C and T = 700 °C due to formation of oxide tribofilms on the surface, which act as a solid lubricant during testing. Проведено исследование влияния давления атмосферы азота на структурно-фазовое состояние и свойства вакуумно-дуговых нитридных покрытий системы Ti-Zr-Hf-V-Nb-Ta. Без учета капельной составляющей, многоэлементные нитридные покрытия, осажденные в азоте, являются однофазными с кубической ГЦК-решеткой (структурный тип NaCl). Наибольшая твердость (42,2 ГПа) достигнута в нитридных покрытиях, осажденных вакуумно-дуговым испарением (Ti, Zr, Hf, V, Nb, Ta) сплава при давлении азота 0,3 Па. Изучены триботехнические характеристики при высокотемпературных испытаниях. Установлено, что при Т = 500 и 700 ºС износостойкость покрытий выше за счет образования окисных трибопленок на поверхности, действующих в качестве твердой смазки в процессе испытаний. Проведено дослідження впливу тиску атмосфери азоту на структурно-фазовий стан і властивості вакуумно-дугових нітридних покриттів системи Ti-Zr-Hf-V-Nb-Ta. Без урахування крапельної складової, багатоелементні нітрідні покриття, осаджені в атмосфері азоту, є однофазними, з кубічною ГЦК-решіткою (структурний тип NaCl). Найбільшої твердості (42,2 ГПа) досягнуто у нітридних покриттях, осаджених вакуумно-дуговим випаровуванням (Ti, Zr, Hf, V, Nb, Ta) сплаву при тиску азоту 0,3 Па. Вивчено триботехнічні характеристики при високотемпературних випробуваннях. Встановлено, що при Т = 500 і 700 ºС зносостійкість покриттів вище за рахунок утворення окисних трібоплівок на поверхні, що діють в якості твердого змащувача в процесі випробувань.